2004
DOI: 10.1142/s0219649204000900
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting IT-Based Knowledge Management Strategy in UK Healthcare System

Abstract: The technological development by the beginning of the 21st century is making it humanly impossible for unaided healthcare professionals to possess all the knowledge needed to deliver medical care with the efficacy and safety made possible by current scientific knowledge. Several healthcare organizations are adopting rigorous methods and technologies for KM as a potential solution to the knowledge predicament. However, awareness and understanding of such methods are not widespread with critics claiming that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Most of the health professionals have imagined that some clinical processes are at risk when they use new technologies. [ 25 ]…”
Section: Resultsmentioning
confidence: 99%
“…Most of the health professionals have imagined that some clinical processes are at risk when they use new technologies. [ 25 ]…”
Section: Resultsmentioning
confidence: 99%
“…The issues of mistrust in computerized data was also raised by Guah and Currie (2004) and Bower et al (2001), who studied the use of ICTs as a way of building cross‐professional and cross‐disciplinary boundaries. They found that the uptake and application of such ICTs was fundamentally affected by a range of social and operational issues, such as fears over a new formalization and traceability of previously informal conversations, a rebalancing of power relationships (between professionals using the ICTs and between doctor and patient), pressures on social/cultural and procedural alignment between participants, and personal attitudes to the technologies, i.e.…”
mentioning
confidence: 99%
“…Establishing trust in KM systems and providing adequate confidentiality and security measures are of special concern in health care and so are particularly challenging; indeed different researchers raised concerns regarding the formalization and traceability of conversations through KM systems (Guah & Currie, 2004;Nicolini, Powell, Conville, & Martinez-Solano, 2008). Besides, the well known time pressure in the health sector, due to a shortage in health professionals, is a particular barrier to the implementation of KM in health care; indeed, the use of IT and KM tools will be perceived as cumbersome unless adequate usability consideration and innovative interfaces are developed for KM systems.…”
Section: Challengesmentioning
confidence: 99%